Effects of prior air pollution exposure on functional recovery after a myocardial infarction - Jordi Bañeras; Alejandro Berenguel-Senén; Eulogio Pleguezuelos; José Antonio Alarcón; Jesús Vallejo; Paz Sanz-Ayán; Juan Izquierdo-García; José Garcia; Rafael Colman; Juan Ignacio Castillo-Martín; Eduard Ródenas-Alesina (Heliyon)
Air pollution is a major cardiovascular risk factor leading to higher rates of heart failure and myocardial infarction (MI), but its effects on functional recovery after an MI remain unknown. Cardiac rehabilitation is a cornerstone of post-MI care and leads to better performance and quality of life, but its benefits may be hampered in heavily polluted environments. To assess the effect of different pollutants on post-MI rehabilitation, we included 137 post-MI patients from 7 Spanish hospitals that were enrolled in a cardiac rehabilitation program who underwent two cardiopulmonary exercise tests (CPET) within a 12-week period. Air pollution data were obtained from preexistent databases and matched with the patient's zip code. Patients exposed to higher NO2 levels (>22.5 ppb, above the median exposure of the cohort) had less improvement in peak oxygen consumption (0.9 % vs 9.5 %, p = 0.014), in oxygen pulse (0.0 % vs 6.9 %, p = 0.034) and tidal volume (−3.7 % vs 4.0 %). PM2.5 and PM10 did not have an impact on CPET parameters. After adjusting by age, sex, active smoking, hypertension, diabetes, hemoglobin, beta-blockers and left ventricular ejection fraction at discharge, the association between high NO2 levels and the change in peak VO2 remained significant (p = 0.029). This study highlights the importance of air pollution during cardiac rehabilitation and suggests that NO2 negatively impact on post-MI functional recovery.